1994
DOI: 10.1037/0033-2909.116.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of male batterers: Three subtypes and the differences among them.

Abstract: Previous typologies of male batterers, including typologies developed by means of rational-deductive and empirical-inductive strategies, are reviewed. On the basis of this review, 3 descriptive dimensions (i.e., severity of marital violence, generality of the violence [toward the wife or toward others], and psychopathology/personality disorders) that consistently have been found to distinguish among subtypes of batterers are identified. These dimensions are used to propose a typology consisting of 3 subtypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

79
1,154
10
50

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,153 publications
(1,293 citation statements)
references
References 79 publications
79
1,154
10
50
Order By: Relevance
“…The overlap we found between IPV, same-sex aggression and controlling behavior also relates to typology studies that have suggested that IPV can be part of a more generally aggressive interpersonal style (e. g., Holtzworth-Munroe & Stuart, 1994;LanghinrichsenRohling, 2010). This is further supported by studies of bullying suggesting that it shares similar risk factors to IPV perpetration.…”
Section: Discussionsupporting
confidence: 73%
“…The overlap we found between IPV, same-sex aggression and controlling behavior also relates to typology studies that have suggested that IPV can be part of a more generally aggressive interpersonal style (e. g., Holtzworth-Munroe & Stuart, 1994;LanghinrichsenRohling, 2010). This is further supported by studies of bullying suggesting that it shares similar risk factors to IPV perpetration.…”
Section: Discussionsupporting
confidence: 73%
“…Our data must be considered together with previous reports related to mental health that were assessed qualitatively by trained researchers, the objective reports obtained by SCL-90 scores, and the participants' court records to assess any history of violence. We suggest that endocrine, psychological, and neuropsychological specific biases should be included in the "family-only" (FO) type, as proposed by Holtzworth-Munroe and Stuart (1994), for individuals whose violent behavior is confined to the home. IPV perpetrators normally behave in a nonaggressive way in non-domestic contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that typologies will also help identify different etiological mechanisms of partner violence (Gottman et al, 1995;Holtzworth-Munroe & Stuart, 1994). Therefore, it seems only natural that the typology approach has drawn a great deal of attention from researchers in the area, particularly from clinicians.…”
mentioning
confidence: 99%
“…Rather, we discuss some of the major and most influential typologies in the field. For such reviews, the reader is referred to Cavanaugh and Gelles (2005), Holtzworth-Munroe and Stuart (1994), and HoltzworthMunroe, Meehan, Herron, Rehman, and Stuart (2003). Second, we outline a dyadic model of couples aggression and the ways that such a model may be more helpful in conceptualizing the development of the behavior over time, including issues of persistence and desistance.…”
mentioning
confidence: 99%